Race/ethnicity, negative peer support, and polyvictimization among college women - DeKeseredy, Walter S. (Journal of ethnicity in criminal justice, 2023)
Advances in social scientific understandings of female racial/ethnic minority college students’ experiences of woman abuse have not kept pace with the amount of theoretical and empirical work on the plight of their White counterparts. What is especially needed is a study that examines racial/ethnic variations in negative peer support for various types of victimization in institutions of higher learning. Using the Campus Quality of Life Survey, results show (1) no significant differences between White and racial/ethnic minority women students in polyvictimization within types of abuse (i.e., stalking, harassment, sexual assault, and intimate partner violence), but some differences in overall rates of victimization and polyvictimization, and (2) negative peer support is strongly related to woman abuse and polyvictimization. Implications are discussed.